1992
DOI: 10.1002/ajmg.1320430162
|View full text |Cite
|
Sign up to set email alerts
|

Clasped‐thumb mental retardation (MASA) syndrome: Confirmation of linkage to Xq28

Abstract: We describe a 5-generation Hispanic family with 13 males and 1 female affected with MASA syndrome. The proposita, a 17-year-old female, and her affected male relatives shared many of the cognate manifestations--mental retardation (14/14), aphasia or delayed speech (13/13), shuffling gait (8/13), adduction of thumbs (14/14)--as well as scoliosis (2/13) and increased deep tendon reflexes in the lower extremities (10/13). Southern analysis with the polymorphic DNA probes DXS14 (Xp11), DXS72 (Xq21), and F8C (Xq28)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
(9 reference statements)
2
13
0
Order By: Relevance
“…Adducted thumbs are typically present at birth and might be due to failure of innervation of the adductors in the forearm (Holtzman et al, 1976; Kanemura et al, 2006). Macias et al found the human mutation (S1181X) that causes the truncation of L1 protein, similar to our L1 1180 mice (Macias et al, 1992; Weller and Gartner, 2001). This human mutation did not cause hydrocephalus or corpus callosum hypoplasia, but it did cause spastic paraplegia and adducted thumbs.…”
Section: Discussionsupporting
confidence: 89%
“…Adducted thumbs are typically present at birth and might be due to failure of innervation of the adductors in the forearm (Holtzman et al, 1976; Kanemura et al, 2006). Macias et al found the human mutation (S1181X) that causes the truncation of L1 protein, similar to our L1 1180 mice (Macias et al, 1992; Weller and Gartner, 2001). This human mutation did not cause hydrocephalus or corpus callosum hypoplasia, but it did cause spastic paraplegia and adducted thumbs.…”
Section: Discussionsupporting
confidence: 89%
“…Carrier detection can be performed by DNA linkage analysis with distal Xq28 markers, if the family is large enough and if there is (are) male patient(s) alive. In females minor features of the spectrum can be found such as adducted thumbs and subnormal intelligence or even the full-blown clinical picture of MASA syndrome [7,25,28,36,45]. If DNA linkage analysis is not possible, an a priori recurrence risk can be calculated from the pedigree.…”
Section: Nonsyndromic Forms Of Hydrocephalus (Table 1)mentioning
confidence: 99%
“…MATERIALS AND METHODS Transformed lymphocyte cultures were prepared from the relatives indicated in Figure 2 and DNA was extracted as described (Macias et al, 1992). DNA linkage studies employed the probes DXS72 (Xq2l-Hind I11 polymorphism) and F8C (Xq28-BcZ I polymorphism).…”
Section: Clinical Reportmentioning
confidence: 99%
“…DNA linkage studies employed the probes DXS72 (Xq2l-Hind I11 polymorphism) and F8C (Xq28-BcZ I polymorphism). Southern analysis and probe labeling were as described (Macias et al, 1992).…”
Section: Clinical Reportmentioning
confidence: 99%